Plant food consumption and emotional well-being: the Helsinki Health Study among 19–39-year-old employees - Elina Mauramo; Tea Lallukka; Noora Kanerva; Jatta Salmela (BMC Nutrition)
Abstract Background and objectives Associations between fruit and vegetable consumption and mental health have been observed, but studies comparing different types of plant foods are sparse. This study among Finnish municipal employees examined associations of the consumption of a range of different plant foods with emotional well-being (EWB). Data and methods We used survey data from the Helsinki Health Study conducted in 2017 among 19–39-year-old employees of the City of Helsinki, Finland (N = 5898, response rate 51.5%, 80% women). Consumption of plant foods, including fruit, berries, fresh and cooked vegetables and wholegrain bread, was measured by a food frequency questionnaire and dichotomised into daily/non-daily consumption. The EWB scale of the RAND-36 questionnaire was dichotomised, with the lowest quartile indicating ‘poor EWB’ and the three higher quartiles indicating ‘good EWB’. We used logistic regression for analysing the associations between plant food consumption and EWB. Analyses were sex-stratified and age, socioeconomic circumstances and psychosocial working conditions were adjusted for. Results Prevalence of daily consumption of plant foods varied from 25% for berries and cooked vegetables to 70% for fresh vegetables. Daily consumption was associated with good EWB among both women and men. The strongest age-adjusted association was found for fresh vegetables, with women (OR 1.48, 95% CI 1.27–1.74) and men (OR 1.86, CI 1.37–2.52) with daily consumption having clearly higher odds of good EWB compared to non-daily consumers. Associations slightly attenuated but mostly remained after adjusting for socioeconomic circumstances and working conditions. Conclusions More frequent plant food consumption was associated with good EWB. Thus, the results support the need for interventions that investigate whether the promotion of plant food consumption could show potential mental health benefits among employees.